2008
DOI: 10.1111/j.1745-3933.2008.00455.x
|View full text |Cite
|
Sign up to set email alerts
|

Redshift-dependent lag—luminosity relation in 565 BATSE gamma-ray bursts

Abstract: We compared redshifts zY measured from the Yonetoku relation and zlag from the lag–luminosity relation for 565 BATSE gamma‐ray bursts (GRBs) and were surprised to find that the correlation between these two redshifts is very low. Assuming that the luminosity is a function of both zY and the intrinsic spectral lag τlag, we found a new redshift‐dependent lag–luminosity relation L= 7.5 × 1050 erg s−1 (1 +z)2.53τ−0.282lag with the correlation coefficient of 0.77 and the chance probability of 7.9 × 10−75. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 20 publications
(37 reference statements)
1
20
0
Order By: Relevance
“…Massaro et al (2008) investigated the cosmological relation between the GRB energy index and the redshift, and presented a statistical analysis of the Amati relation searching for possible functional biases. Tsutsui et al (2008) reported a redshift dependence of the lag-luminosity relation in 565 BASTE GRBs. Oguri & Takahashi (2006) and Schaefer (2007) discussed the gravitational lensing and Malmquist biases of GRBs, and found that the biases are small.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Massaro et al (2008) investigated the cosmological relation between the GRB energy index and the redshift, and presented a statistical analysis of the Amati relation searching for possible functional biases. Tsutsui et al (2008) reported a redshift dependence of the lag-luminosity relation in 565 BASTE GRBs. Oguri & Takahashi (2006) and Schaefer (2007) discussed the gravitational lensing and Malmquist biases of GRBs, and found that the biases are small.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In general they migrate to later times and become wider going to lower energy, although some GRBs with the opposite trend have been observed ). This so-called "spectral lag" correlates with the peak flux of the GRBs (Norris et al 2000;Norris 2002;Tsutsui et al 2008): long spectral lags have been measured mainly in GRBs with low peak fluxes, while short spectral lags have been observed in bursts with both high and low peak fluxes. Based on these findings, one can divide GRBs in three groups: bright with short lags, faint with short lags, and faint with long lags.…”
Section: On the Relation Between Spectral Lags And Peak Fluxesmentioning
confidence: 97%
“…Most of the previous work on spectral lags has been based on observations with the Burst and Transient Source Experiment (BATSE) on the Compton Gamma Ray Observatory (Tsutsui et al 2008;Hakkila et al 2008Hakkila et al , 2007Chen et al 2005;Band et al 2004; Salmonson & Galama 2002;Norris 2002;Band 1997). The launch of the Swift satellite (Gehrels et al 2004) ushered in a new era of GRB research.…”
Section: Introductionmentioning
confidence: 99%